Unlocking contract law - Turner, Chris . (Barrister); Hodge, Sue. (Abingdon, Oxon ; New York, NY : Routledge, 2004)
"The Unlocking the Law series makes the law accessible. Each chapter contains activities such as quick quizzes and self-test questions, key facts charts to consolidate your knowledge and diagrams to aid learning. Cases, judgments and primary source quotations are prominently displayed. Summaries help you understand each chapter, there is a glossary of legal terminology. New features include problem questions with guidance on answering, as well as essay questions and answer plans, plus cases and materials exercises. All titles in the series follow the same formula and include the same features so students can move easily from one subject to another. www.unlockingthelaw.co.uk provides free resources such as multiple choice questions, key questions and answers, revision mp3s and cases and materials exercises"--
"Contract law is a core element of all law degrees in England and Wales. Unlocking Contract Law will ensure you grasp the main concepts with ease. This book explains the facts and associated case law for: The rules regarding formation of contracts The contents of a contract Vitiating factors, factors which invalidate an otherwise validly formed contract The rules on discharge of contractual obligations Available remedies"--
Includes index.
Keywords: Contracts -- England; Contracts -- Wales; LAW / General